O PLANO TERRITORIAL DE DESENVOLVIMENTO RURAL SUSTENTÁVEL (PTDRS) - TERRITÓRIO NOROESTE PAULISTA (SP): PLANEJAMENTO E GESTÃO - Oliveira, Luciana Carvalho de [UNESP]; Arana, Alba Regina Azevedo; Sant’ana, Antonio Lázaro [UNESP] (Editora da Universidade Federal de Uberlândia - EDUFU, 2022)
This article approach the history of the development of the Território Rural Noroeste Paulista (Northwest Rural Territory of São Paulo) and the development, management and implementation of Plano Territorial de Desenvolvimento Rural Sustentável do Território Noroeste Paulista (Territorial Plan for Sustainable Rural Development of Northwest Territory of São Paulo), from research that analyzed the Programa Nacional de Desenvolvimento Sustentável de Territórios Rurais (National Program of Sustainable Development of Rural Territories) in said Territory. It has been used three main instruments: literature review, field notebook and documental research. The formation of the Territory was the result of a joint in the region and it has constantly made efforts for mobilization and sensitization of social actors. The preparation of the Territorial Plan was successful, however the Territory still faces many difficulties related to the management and implementation.

Este artigo aborda o processo histórico de formação do Território Rural Noroeste Paulista e a elaboração, gestão e execução do Plano Territorial de Desenvolvimento Rural Sustentável do Território Noroeste Paulista, a partir de pesquisa que analisou o Programa Nacional de Desenvolvimento de Territórios Rurais no referido Território. Recorreu-se a três instrumentos principais: levantamento bibliográfico, caderno de campo e pesquisa documental. A formação do Território foi fruto de uma articulação da região e o mesmo tem realizado permanentemente esforços de mobilização e sensibilização dos atores sociais. A elaboração do Plano Territorial foi realizada com êxito, no entanto o Território ainda enfrenta muitas dificuldades relacionadas à gestão e execução do mesmo.
The territorial plan of sustainable rural development (PTDRS) - Northwest Territory of São Paulo (SP): planning and management.
Keywords: Planning; Public Policies; Territorial Development; Pronat; Planejamento; Políticas Públicas; Desenvolvimento Territorial; Pronat